I'm a stay at home businesswoman: An insight into informal entrepreneurship in Jordan - Mehtap, Salime (2019)
Women and disadvantaged minorities within emerging and developing economies often resort to business activity within the informal economy as a way to overcome various barriers and challenges to formal workforce participation. This paper aims to explore the characteristics, motives, barriers and challenges of female engagement in informal business activities in Jordan.